Isotropic cell design enables low-pressure lithium metal solid-state batteries - William Fitzhugh; Luhan Ye; Xin Li (Electrochemistry Communications, 2024)
Solid-state batteries that utilize sulfide-based solid-electrolytes, such as the argyrodite Li6PS5Cl, have become one of the most promising directions for next-generation energy storage. However, one remaining technical challenge for such materials has been the requirement of large pressures during operation. This challenge grows as the size of the cells increase as the pressure must be uniformly distributed over a larger-and-larger area. In this work, we introduce an isotropic cell design to pressurize the cell with perfect homogeneity, which is ensured by using a fluid pressurization medium. By achieving perfect homogeneity, the magnitude of the pressure necessary to stabilize the material is greatly reduced. Using such an isotropic cell design, lithium-metal solid-state pouch cells achieve remarkable extreme-fast-charging performance even at a low-pressure of only 2 MPa.